2016
DOI: 10.1177/2054270416663569
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric patients in intensive care unit: Perspective from a teaching hospital in Pakistan

Abstract: ObjectiveReview of obstetric cases admitted to the intensive care unit.DesignTen year retrospective review of individual patients' medical records.ParticipantsRecords of obstetric patients admitted from 2005–2014.SettingAga Khan University Hospital KarachiMain Outcome measuresDiagnosis at the time of admission, associated risk factors, and intervention required aspects of management and rate of mortality.FindingsA total of 194 obstetric patients were admitted out of which 86.2% of patients had ventilator suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 31 publications
(33 reference statements)
1
25
1
Order By: Relevance
“…In a study by Leung et al, the mode of admission was elective in 12% and emergency in 88% patients (Leung et al, 2010). Qureshi et al reported, the source of admission was the emergency department in 38.14% and obstetrics and gynecology department in 61.85% patients (Qureshi et al, 2016). Although, our SICU is a tertiary care unit, which receives referrals from other hospitals, there was no outside referral during the said study period.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In a study by Leung et al, the mode of admission was elective in 12% and emergency in 88% patients (Leung et al, 2010). Qureshi et al reported, the source of admission was the emergency department in 38.14% and obstetrics and gynecology department in 61.85% patients (Qureshi et al, 2016). Although, our SICU is a tertiary care unit, which receives referrals from other hospitals, there was no outside referral during the said study period.…”
Section: Discussionmentioning
confidence: 81%
“…Septic shock and anesthesia complication were the causes in 12.3% and 2.9% patients in a study by Verma and Rathore (2014). In a study by Qureshi et al (2016), septic shock and anesthesia complication were seen in 56% and 4.2% patients, respectively. Whereas, septic shock was seen in 2.94% of patients in a study by Sharma et al (2016).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations